Against The Practice of Money Politics: An Analysis of The Potential For Bribery Prevention In The Conduct of Elections - Suryaningsi, Suryaningsi; Putri, Novita Amelia (Journal of Mujaddid Nusantara, 2024)
This article examines the prevalence of money politics during local elections in Samarinda City, offering a comprehensive analysis of Article 187A from the 2017 Election Law. The objective is to assess the impact of money politics on electoral integrity and democratic principles, alongside evaluating the efficacy of Article 187A in mitigating these challenges. Employing a qualitative approach with a case study design, the research integrates interviews with officials from the East Kalimantan Election Supervisory Agency and direct observation of money politics cases in Samarinda City. The findings reveal that money politics compromises election integrity and undermines democratic ideals. Despite the potential of Article 187A to address these issues, its implementation encounters significant hurdles. In conclusion, rigorous measures are imperative to combat money politics and enforce electoral laws, ensuring fairness and integrity in the electoral process. The research underscores the necessity for enhanced implementation of Article 187A and heightened public awareness to counteract the influence of money in elections.